Cellular Clearance and Biological Activity of Calciprotein Particles Depend on Their Maturation State and Crystallinity - Köppert, Sina; Büscher, Andrea; Babler, Anne; Ghallab, Ahmed; Buhl, Eva M.; Latz, Eicke; Hengstler, Jan G.; Smith, Edward R.; Jahnen-Dechent, Willi (Frontiers in Immunology, 2018)
Background: The liver-derived plasma protein fetuin-A is a systemic inhibitor of ectopic calcification. Fetuin-A stabilizes saturated mineral solutions by forming colloidal protein-mineral complexes called calciprotein particles (CPP). CPP are initially spherical, amorphous and soft, and are referred to as primary CPP. These particles spontaneously convert into secondary CPP, which are larger, oblongate, more crystalline and less soluble. CPP mediate excess mineral transport and clearance from circulation. Methods: We studied by intravital two-photon microscopy the clearance of primary vs. secondary CPP by injecting i.v. synthetic fluorescent CPP in mice. We analyzed CPP organ distribution and identified CPP endocytosing cells by immunofluorescence. Cellular clearance was studied using bone marrow-derived mouse wildtype and scavenger receptor A (SRA)-deficient macrophages, as well as human umbilical cord endothelial cells (HUVEC), monocyte-derived macrophages (hMDM), and human aortic endothelial cells (haEC). We employed mouse wildtype and mutant immortalized macrophages to analyze CPP-induced inflammasome activation and cytokine secretion. Results: In live mice, only primary CPP were rapidly cleared by liver sinusoidal endothelial cells (LSEC), whereas primary and secondary CPP were cleared by Kupffer cells. Scavenger receptor A (SRA)-deficient bone marrow macrophages endocytosed secondary CPP less well than did wildtype macrophages. In contrast, primary CPP endocytosis did not depend on the presence of SRA, suggesting involvement of an alternative clearance pathway. CPP triggered TLR4 dependent TNFa and IL-1b secretion in cultured macrophages. Calcium content-matched primary CPP caused twice more IL-1b secretion than did secondary CPP, which was associated with increased calcium-dependent inflammasome activation, suggesting that intracellular CPP dissolution and calcium overload may cause this inflammation. Conclusions: Secondary CPP are endocytosed by macrophages in liver and spleen via SRA. In contrast, our results suggest that primary CPP are cleared by LSEC via an alternative pathway. CPP induced TLR4-dependent TNFa and inflammasome-dependent IL-1b secretion in macrophages suggesting that inflammation and calcification may be considered consequences of prolonged CPP presence and clearance.